The added value of health-related quality of life as a prognostic indicator of overall survival and progression-free survival in glioma patients: a meta-analysis based on individual patient data from randomised controlled trials. (July 2019) - Coomans, Marijke; Dirven, Linda; K. Aaronson, Neil; Baumert, Brigitta G.; van den Bent, Martin; Bottomley, Andrew; Brandes, Alba A.; Chinot, Olivier; Coens, Corneel; Gorlia, Thierry; Herrlinger, Ulrich; Keime-Guibert, Florence; et al.
Abstract: Objective: Prognostic value of health-related quality of life (HRQoL) data may be important to inform patients in clinical practice and to guide clinical decision-making. Our study investigated the added prognostic value of HRQoL for overall survival (OS) and progression-free survival (PFS) in a large heterogeneous sample of glioma patients, besides known prognostic factors. Methods: We included individual baseline data from previously published randomised controlled trials (RCTs) in glioma patients in which HRQoL was assessed through the European Organisation for Research and Treatment of Cancer QLQ-C30 and QLQ-BN20 questionnaires. Multivariable Cox regression models (stratified for newly diagnosed versus recurrent disease) were constructed, first with clinical variables (age, sex, tumour type, performance status, allocated treatment and extent of resection) only and subsequently with HRQoL variables added, separately for OS and PFS. The added prognostic value of HRQoL was calculated using C-indices. Results: Baseline HRQoL and clinical data from 15 RCTs were included, comprising 5217 patients. In the model including both clinical and HRQoL variables, better cognitive and role functioning and less motor dysfunction were independently associated with longer OS, whereas better role and cognitive functioning, less nausea and vomiting and more appetite loss were independently associated with prolonged PFS. However, C-indices indicated only a small prognostic improvement of the models for OS and PFS when adding HRQoL to the clinical prognostic variables (+1.1% for OS and +.7% for PFS). Conclusion: Our findings demonstrate that several baseline HRQoL variables are independently prognostic for OS and PFS, yet the added value of HRQoL to the known clinical prognostic variables was small. Highlights: Several HRQoL scales were found to be independently prognostic for overall survival (OS) and progression-free survival (PFS). Better cognitive functioning and role functioning and less motor dysfunctioning were independently associated with longer OS. Better role and cognitive functioning, less nausea and vomiting and more appetite loss were independently associated with prolonged PFS. Yet the added value of HRQoL to the known clinical prognostic variables was small: 1.1% for OS and .7% for PFS. Subgroup analyses showed that different HRQoL scales/items were independently prognostic for OS and PFS.